Efficacy and Safety of Chemotherapy or EGFR‐TKIs as First‐Line Therapy in NSCLC Patients Harboring Non‐Ex 20 Ins Uncommon EGFR Mutations: A Retrospective Study in China - Chen Liao; Li Bai; Tingting He; Qingle Liang; Defeng Hu; Shipeng Lei; Yong He; Yubo Wang (Cancer Medicine)
ABSTRACT Background Uncommon EGFR mutations are a kind of heterogeneous group of mutations with various responses to EGFR‐TKIs and are often excluded from most prospective clinical trials. In this real‐world retrospective study, we retrospectively compared the efficacy and safety of chemotherapy or various generations of EGFR‐TKIs as first‐line therapy in NSCLC Chinese patients harboring non‐ex 20 ins uncommon EGFR mutations. Methods We enrolled 139 NSCLC patients with non‐ex 20 ins uncommon EGFR mutations in this study retrospectively. Patients' clinical characteristics and the efficacy and safety of different first‐line therapies were analyzed and compared. Results Our data reviewed that for first‐line therapy, NSCLC patients harboring non‐ex 20 ins uncommon EGFR mutations benefited more from EGFR‐TKIs compared with chemotherapy. Afatinib performed with great efficacy for the majority of non‐ex 20 ins uncommon EGFR mutations (N = 43, ORR = 41.86%, mPFS = 13.5 months, mOS = 20.8 months), especially in L861Q mutation (mPFS = 18.4 months). Osimertinib also demonstrated efficacy in patients harboring non‐ex 20 ins uncommon EGFR mutations (N = 36, ORR = 27.78%, mPFS = 10.0 months, mOS = 21.0 months), especially in those without L861Q and G719X mutations (mPFS = 12.1 months). When treated with afatinib, patients harboring non‐ex 20 ins uncommon EGFR mutations should pay attention to the management of safety, especially for gastrointestinal‐related AE and rash, while osimertinib was safer. Conclusion Taking into account both efficacy and safety, afatinib and osimertinib are better choices than chemotherapy and first‐generation EGFR‐TKIs for NSCLC patients with non‐ex 20 ins uncommon EGFR mutations. L861Q showed a trend toward a better response to afatinib, while in those without L861Q and G719X mutations, osimertinib might be a better choice. Safety also should be a concern when choosing EGFR‐TKI for treatment, patients should pay attention to the management of safety when using afatinib while osimertinib is safer.